Hybrid Molecules: Promising Compounds for the Development of New Treatments Against Leishmaniasis and Chagas Disease - Cardona-G, Wilson; Yepes, Andres F.; Herrera-R, Angie (Current Medicinal Chemistry, 2018)
Leishmaniasis and Chagas disease are endemic pathologies in tropical countries. These cause high morbidity and a public health problem. Current chemotherapies are based on conventional drugs with variable efficacy and toxicity related with the length of therapeutic schemes and high doses. When two pharmacological agents are combined into a single molecule, the result is the so-called hybrid molecule. In the search for new treatments against Chagas disease and leishmaniasis, several studies have shown that hybrid molecules display high antiprotozoal activity and this emerging strategy is quite promising in the field of new drug discovery and development. This review focuses on the antiprotozoal activity of different hybrids obtained from the hybridization of pharmacophores, showing that the most of the efforts have been concentrated in the molecular hybridization of quinoline, chalcone and hydrazone moieties.
Keywords: trypanosomiasis